Kloning Gen Coat Protein SMV dengan Pendekatan PCR - Sismindari Sismindari; Sudjadi Sudjadi (Jurnal Perlindungan Tanaman Indonesia, 1996)
SMV is RNA virus had to be converted to the first strand DNA using oligo (dT) and murine reverse transcriptase. Amplification of coat protein gene region was carried out by Polimerase Chain Reaction (PCR) with two primers, 5’-TACATCTTGGAACCAATGGCAGGCAAGGAGAGAAG-3’ and 5’-AGGACAACAAACATTGCCG-3’. The PCR product was blund ended by S1 nuclease, and ligated into SmaI digested pUC18 and phosphatase treatment by calf intestine phosphatase. Ligation mixture was used to transform E. coli DH5α. Recombinant plasmid was digested with EcoRI and HindIII showed 0,8 kb fragment. Southern blot analysis at high strigency using PCR using PCR product as a probe shows that the 0,8 kb fragment produced intense signal.